Training Networks of Local Health Departments: A Regional Assessment. Issue 1 (12th January 2022) - Harris, Jenine K.; Leider, Jonathon P.; Kulik, Phoebe; Beck, Angela
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: The public health system faces major challenges in 2020, including an aging workforce, reductions in funding, and 2 simultaneous major threats to public health—the coronavirus pandemic and racial injustice. To effectively harness promising new technologies and address these and other public health challenges ahead, public health professionals must be trained on evidence-based practices for protecting and improving public health. This project sought to understand the network of health departments and organizations that provide training in order to inform strategic efforts to fill training gaps and improve access to training for local health departments (LHDs), thereby strengthening the public health system. Design/Setting/Participants: We conducted a Web-based survey of 501 LHDs in the 6 states constituting Region V of the Department of Health & Human Services. The survey focused on the training relationship between LHDs and state and national organizations that provide public health training, allowing for a social network analysis. We used data visualization and descriptive statistics to examine the network. Results: Of 290 participating health departments (58% response rate), 248 had monthly or more frequent contact with at least 1 organization for the purpose of training. Altogether, the 248 LHDs were connected to 47 state-level organizations and 10 national-level organizations. In 5 of 6 states, more LHDs were connected to the state health department for training than to any other organization type. Universities, national nonprofits, and national membership organizations provided training to the fewest LHDs. Local health department characteristics did not have a clear relationship with its number of training connections. Conclusions: State health departments may benefit from the support of universities, national nonprofits, and national membership organizations by partnering to offer training or by recommending training from these organizations to LHDs. Additional qualitative information from local and state health departments would be useful to determine the best strategies for universities, national nonprofits, and national membership organizations to participate in training local practitioners to improve LHD capacity.